2023
DOI: 10.3390/microorganisms11102439
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Genotypic Characterization of Recently Isolated Multidrug-Resistant Acinetobacter baumannii Clinical and Aquatic Strains and Demonstration of Silver Nanoparticle Potency

Irina Gheorghe-Barbu,
Viorica Maria Corbu,
Corneliu Ovidiu Vrancianu
et al.

Abstract: This study aims to demonstrate the effectiveness of silver nanoparticles (Ag NPs) on multidrug-resistant (MDR) Acinetobacter baumannii (AB) strains isolated from the clinical and aquatic environment. Three types of Ag NPs were investigated for their antimicrobial, antibiofilm, and antivirulence properties on a total number of 132 AB strains isolated in the same temporal sequence from intra-hospital infections (IHIs), wastewater (WW), and surface water (SW) samples between 2019 and 2022 from different Romanian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…The reagents isopropyl alcohol, NH 3 solution 25%, hydrogen peroxide 35%, HCl 37%, MPTMS, and MPTES were purchased from Sigma-Aldrich (Darmstadt, Germany). The dithizone was acquired from Chinoin (Ciudad de Mexico, Mexico), the thioindigo was from (TCI-Tokyo Chemical Industry Co., Tokyo, Japan), and the AgNPs used were synthesized and characterized according to previous studies [17,18]. The AgNPs used in this study were synthesized by the solvothermal method with polyethylene glycol as a reduction component, at 260 • C and 3 bar pressure for 1 h. The results in the case of the solvothermal reaction showed that the nanoparticles were spherical with an average size of 50 nm (HT4 synthesis from our previous paper [17]).…”
Section: Chemicalsmentioning
confidence: 99%
“…The reagents isopropyl alcohol, NH 3 solution 25%, hydrogen peroxide 35%, HCl 37%, MPTMS, and MPTES were purchased from Sigma-Aldrich (Darmstadt, Germany). The dithizone was acquired from Chinoin (Ciudad de Mexico, Mexico), the thioindigo was from (TCI-Tokyo Chemical Industry Co., Tokyo, Japan), and the AgNPs used were synthesized and characterized according to previous studies [17,18]. The AgNPs used in this study were synthesized by the solvothermal method with polyethylene glycol as a reduction component, at 260 • C and 3 bar pressure for 1 h. The results in the case of the solvothermal reaction showed that the nanoparticles were spherical with an average size of 50 nm (HT4 synthesis from our previous paper [17]).…”
Section: Chemicalsmentioning
confidence: 99%